CENTRAL KALIMANTANâS FAST GROWING SPECIES: SUITABILITY FOR PULP AND PAPER - Adi, Danang Sudarwoko; Wahyuni, Ika; Risanto, Lucky; Rulliaty, Sri; Hermiati, Euis; Dwianto, Wahyu; Watanabe, Takashi (Secretariat of Forestry Research and Development Agency, 2015)
Fast growing wood species could be promising to fulfill the gap between wood demand and supply. Due to their low quality, the utilization of fast growing wood species has been limited to pulp and paper. Our previous study on the fiber characteristic and density of the 30 unutilized fast growing wood species from PT Sari Bumi Kusuma, Central Kalimantan, showed that there were five species which could be promising as pulp and paper material. These wood species have fiber lengths of more than 2200 Âµm. This research was conducted to get information another property of the five woods to more discover their potential utilization, especially for pulp and paper material. The wood species investigated were Endospermum diadenum, Dillenia sp., Adinandra dumosa, Adinandra sp., and Nauclea junghuhnii. The results showed that these five species have a long of fiber length, which are classified in Class I, low to medium density, fiber derived value which the total score felt in the class I. The chemical compositions showed that extractive, holocelullose, Î±-cellulose, and lignin contents were 1.74-4.12%, 62.73-73.83%, 37.24-46.97%, 29.68-38.92%, respectively. Based on fiber characteristic, density, and chemical properties, these five species could be used as an alternative raw material for pulp and paper industries.Â